Islamic Fintech Regulation and Competition: Analysis of Their Impact on the Innovation of Islamic Financial Institutions in Indonesia - Shofa Robbani; Windiyanti Laily Nuraini; Fitri Nadziratul Hikmah; Mohammad Naufal Ridlo Fasya; Muhammad Nazir Alias (ASAS, 2026)
This study examines the relationship between Sharia regulation and competition in the Sharia fintech industry in driving innovation within Sharia financial institutions in Indonesia. The development of Sharia fintech places Islamic financial institutions in a complex position because compliance with regulatory frameworks and Sharia principles, including the implementation of contracts (akad), must align with the need for rapid innovation in the digital financial sector. This condition raises the question of whether regulation and Sharia compliance function as enabling instruments for innovation or instead become obstacles to industry development. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. The analysis focuses on Sharia fintech regulations, principles of Sharia compliance, and the implementation of contracts in digital financial services. The findings indicate that adaptive, integrated, and responsive regulation can provide legal certainty, enhance public trust, strengthen consumer protection, and promote sustainable innovation. In contrast, rigid regulatory frameworks and inflexible Sharia compliance mechanisms may hinder technological development, particularly in adapting Sharia contracts to digital platforms. Competition among Sharia fintech providers encourages service efficiency, product diversification, improved user experience, and innovation in developing digital Sharia-compliant contracts. The novelty of this study lies in positioning regulation, competition, and Sharia compliance as interconnected factors shaping innovation. This study recommends strengthening an innovation-oriented Sharia governance model to foster an innovative, competitive, inclusive, and sustainable Sharia fintech ecosystem in Indonesia.